Analisis Framing Berita Perempuan Bakar Diri Dalam Media Online Detik.Com Dan Kompas.Com - Yana, Melinda Defy; Setiawan, Hendra (Peneliti.net, 2023)
The method used in this research is descriptive qualitative method. The results of the study show that there are differences in framing by Detik.com and Kompas.com media, especially in syntactic, thematic and rhetorical elements. In the syntactical aspect, the Detik.com media writes news using serenity where the title of the news is framing using a choice of words that lead to the news content and involve the police in the title which makes people curious about the news. Meanwhile, at Kompas.com, when writing the title, it is interesting with the use of the word